2019
DOI: 10.1016/j.cmi.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and colonization dynamics of antimicrobial-resistant bacteria during international travel: a prospective cohort study

Abstract: Objectives: Travellers may be colonized with antimicrobial-resistant bacteria on return, but little is known about colonization during travel. Our objectives were to assess the acquisition and colonization dynamics during the stay abroad for a broad range of antimicrobial-resistant bacteria and resistance phenotypes and to identify risk factors for faecal carriage of antimicrobial-resistant bacteria. Methods: German and Dutch participants (n ¼ 132) of this prospective cohort study (2016e2018) completed a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…It remains an open question, how likely is it that the transmission of mcr -positive Enterobacterales to humans via the food chain occurs? Despite the high detection rates of mcr genes in water or livestock, a study consecutively testing 132 German travelers recently found that 11.4% of all persons carried mcr - 1 -positive Enterobacterales during and after travel, but none of them were colonized before leaving Germany [ 21 ]. In other European countries, the prevalence of mcr - 1 in the community or among patients in hospitals was also low (0–0.4%) [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains an open question, how likely is it that the transmission of mcr -positive Enterobacterales to humans via the food chain occurs? Despite the high detection rates of mcr genes in water or livestock, a study consecutively testing 132 German travelers recently found that 11.4% of all persons carried mcr - 1 -positive Enterobacterales during and after travel, but none of them were colonized before leaving Germany [ 21 ]. In other European countries, the prevalence of mcr - 1 in the community or among patients in hospitals was also low (0–0.4%) [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It could be that the potential acquisition of ESBL-E in connection with diarrhoea was partially cleared at the time of sampling. A cohort study among 132 German and Dutch travellers who provided daily stool samples before, during, and after travel showed that the number of travellers with a temporary colonisation during the journey exceeded the number of travellers still colonised after return [18].…”
Section: Discussionmentioning
confidence: 99%
“…a selective agar plate method without a pre-enrichment with a broth containing second or third generation cephalosporins (Table 2) [26, 29-31, 35, 36, 39, 42]. In only 4 of these eight studies, a CPE was found [26,31,36,42]. In 13 out of the 22 studies (59.1%), screening for CPE was carried out in isolates or directly on the specimen by a variety of phenotypic and genotypic methods (Table 2).…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…Only one study clearly defined TD as more than 3 loose/liquid stools per 24 h or more frequently than normal for an individual [29] and one study referred to the World Health Organization (WHO) definition [42]. The other included studies just asked in questionnaires if the participant had experienced TD yes or no.…”
Section: Study Characteristicsmentioning
confidence: 99%